First‐in‐man study to investigate safety, pharmacokinetics and exploratory pharmacodynamics of HTL0018318, a novel M1‐receptor partial agonist for the treatment of dementias. Issue 7 (5th February 2021) - Bakker, Charlotte; Tasker, Tim; Liptrot, Jan; Hart, Ellen P.; Klaassen, Erica S.; Prins, Samantha; van der Doef, Thalia F.; Brown, Giles A.; Brown, Alastair; Congreve, Miles; Weir, Malcolm; Marshall, Fiona H.; et al.
Abstract : Aims: HTL0018318 is a selective M1 receptor partial agonist currently under development for the symptomatic treatment of cognitive and behavioural symptoms in Alzheimer's disease and other dementias. We investigated safety, tolerability, pharmacokinetics and exploratory pharmacodynamics (PD) of HTL0018318 following single ascending doses. Methods: This randomized, double‐blind, placebo‐controlled study in 40 healthy younger adult and 57 healthy elderly subjects, investigated oral doses of 1–35 mg HTL0018318. Pharmacodynamic assessments were performed using a battery of neurocognitive tasks and electrophysiological measurements. Cerebrospinal fluid concentrations of HTL0018318 and food effects on pharmacokinetics of HTL0018318 were investigated in an open label and partial cross‐over design in 14 healthy subjects. Results: Pharmacokinetics of HTL0018318 were well‐characterized showing dose proportional increases in exposure from 1–35 mg. Single doses of HTL0018318 were associated with mild dose‐related adverse events of low incidence in both younger adult and elderly subjects. The most frequently reported cholinergic AEs included hyperhidrosis and increases in blood pressure up to 10.3 mmHg in younger adults (95% CI [4.2–16.3], 35‐mg dose) and up to 11.9 mmHg in elderly subjects (95% CI [4.9–18.9], 15‐mg dose). There were no statistically significant effects on cognitive function but the study was not powered to detect small to moderate effect sizes of clinical relevance. Conclusion: HTL0018318 showed well‐characterized pharmacokinetics and following single doses were generally well tolerated in the dose range studied. These provide encouraging data in support of the development for HTL0018318 for Alzheimer's disease and other dementias.